2012
DOI: 10.1080/1369118x.2012.674959
|View full text |Cite
|
Sign up to set email alerts
|

Online Harassment Among College Students

Abstract: A replication incorporating new Internet trends Increased time spent online in combination with current Internet trends such as social networking have led to new risks for online harassment. This problem has been given much attention for adolescents, but little has been done to describe the risks of online harassment experienced by young adults, even though they exhibit Internet behavior comparable to adolescents. This study is in part a replication of a previous study that surveyed online harassment within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 21 publications
3
41
1
7
Order By: Relevance
“…College students indicated cyberbullying made them sad, angry or upset, and caused an increase in stress indicating the psychological impact of cyberbullying does not dissipate as the victim matures. These findings confirm results from previous studies, which indicate cyberbullying can be a catalyst for impaired mental health, psychological distress, provokes fear, and in extreme cases increases risk factors associated with suicide among college populations (Dilmac, 2009;Hartwell-Walker, 2010;Lindsay & Krysik, 2012;Zacchilli & Valerio, 2011).…”
Section: Psychological Impactsupporting
confidence: 93%
“…College students indicated cyberbullying made them sad, angry or upset, and caused an increase in stress indicating the psychological impact of cyberbullying does not dissipate as the victim matures. These findings confirm results from previous studies, which indicate cyberbullying can be a catalyst for impaired mental health, psychological distress, provokes fear, and in extreme cases increases risk factors associated with suicide among college populations (Dilmac, 2009;Hartwell-Walker, 2010;Lindsay & Krysik, 2012;Zacchilli & Valerio, 2011).…”
Section: Psychological Impactsupporting
confidence: 93%
“…An examination of the relationship between online activities and cyberbullying among adolescents aged 12-15 years old by Park et al (2014) found that frequent users of the internet and SNS were more likely to engage in, become victims of, and witness cyberbullying behavior. Lindsay and Krysik (2012) similarly suggest that SNS usage may predict acts of cyberbullying.…”
Section: Literature Reviewmentioning
confidence: 92%
“…This also suggests that the statistical figures about stalking prevalence could very possibly be extensively underreported. Therefore, more research needs to be done in identifying predictors of cyberstalking behavior so that the behavioral traits in perpetrators can be identified at earlier stages to stanch future cyberstalking activities (see Lindsay & Krysik, 2012). Menard and Pincus (2012) have made such an effort by studying 3,609 undergraduates to explore predictors that explain men's and women's stalking and if these predictors are similar for cyberstalking as well as overt stalking.…”
Section: Stalkingmentioning
confidence: 98%